Pengaruh Public Relations Melalui Instagram Reels Dan Brand Identity Terhadap Promosi Produk Yotta_Id - Nina .; Syahruddin .; Abdul Sarlan Menungsa (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study examines the influence of Instagram Reels utilization strategies and brand identity engagement on product promotion effectiveness for the @yotta_id account. It aims to determine how creative short-form audiovisual content and brand identity consistency strengthen product promotion in Kendari. Using a quantitative method, the research tested variables through primary data collection from 94 students at Nahdlatul Ulama University of Southeast Sulawesi (UNUSRA) who are active Instagram users. Data were analyzed via multiple linear regression using SPSS software. Findings indicate that the Instagram Reels variable, characterized by visual quality and content appeal, partially exerts a significant impact on product promotion. Similarly, brand identity positively influences promotion through two-way interaction between followers and the brand. Simultaneously, both variables significantly drive promotional success for @yotta_id. The study concludes that combining creative content with visual and value consistency is a key factor in digital marketing. These results contribute to communication science literature.